Розвиток відновного правосуддя в міжнародному законодавстві - Дубовик, Ольга Ігорівна; Дубовик, Ольга Игоревна; Dubovik, Ol'ga (Одеса : Юрид. л-ра, 2014)
The article is devoted to the analyses of development of restorative justice in the international law. The restorative justice fundamentals are enshrined in international instruments of the United Nations and the Council of Europe. Special attention in the United Nations international regulations containing general provisions on restorative justice is given to the right to use an alternative to court proceedings, mediation, conciliation. This right for the person is represented both as a duty of the United Nations member-states to consolidate and implement it in the national law.
Дубовик О. І. Розвиток відновного правосуддя в міжнародному законодавстві / О. І. Дубовик // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 322-325.
Keywords: відновне правосуддя; медіація; міжнародне право; ООН; Рада Європи; система кримінального судочинства; альтернативное правосудие; медиация; международное право; Совет Европы; система криминального судопроизводства; restorative justice; mediation; international law; United Nations; Council of Europe; criminal justice system